1996
DOI: 10.1177/026309239601500102
|View full text |Cite
|
Sign up to set email alerts
|

Hygienic Assessment of Low Frequency Noise Annoyance in Working Environments

Abstract: Different ways of assessing low frequency noise below the level of hearing damage to predict noise annoyance are treated. Three methods for classification of low frequency noise are tested. Some assessment methods, e.g. low frequency noise ratings (LFNR), frequency weightings A - D, the difference dB(C) - dB(A) and Zwicker loudness, are presented and evaluated regarding their relation to rated annoyance. Low frequency noise groups were selected out of 338 recordings from different occupational environments, e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…in the 25-to 50-Hz range). This disagreement was consistent with many previous studies which have reported that the A-weighted sound pressure level is insufficient for evaluating lowfrequency noise 11,12,[14][15][16][17] . The correlation coefficient calculated for the 'best-fit' frequency-weighted sound pressure level (SPL W ) is also listed in Table 2.…”
Section: Fig 3 Frequency-independent Correlations Between the Mean supporting
confidence: 91%
See 2 more Smart Citations
“…in the 25-to 50-Hz range). This disagreement was consistent with many previous studies which have reported that the A-weighted sound pressure level is insufficient for evaluating lowfrequency noise 11,12,[14][15][16][17] . The correlation coefficient calculated for the 'best-fit' frequency-weighted sound pressure level (SPL W ) is also listed in Table 2.…”
Section: Fig 3 Frequency-independent Correlations Between the Mean supporting
confidence: 91%
“…However, it is well known that low-frequency noise often causes unpleasantness or annoyance 7) . These adverse psychological effects can be induced even by low-level low-frequency noise in living environments 8,9) and they are expected to be more prevalent in working environments where high-level low-frequency noises are generated [10][11][12] . Inukai et al 13) reported that the slopes of the equalunpleasantness level contours are very similar to those of the equal-loudness level contours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…where a, b, and are numerical constants (Vos, 2001) The expression (C-A)>15 has been widely used as an identifier of LFN (see Holmberg et al 1997) With the above in mind, an equation has been derived for LFN, and is put forward as follows; L = A + (0.84A-29.44) + 0.04(C-A)(41-A)…”
Section: Journal Of Low Frequency Noise Vibration and Active Controlmentioning
confidence: 99%
“…Different assessment methods; low frequency noise ratings (LFNR), frequency weighings A -D, the difference dBC -dBA methods and Zwicker loudness, have been evaluated regarding their relation to rated annoyance (Holmberg et al 1996). According to the results, the correlations between annoyance and weighted values, linear values, sone values and the dBC -dBA difference are poor, None of the methods seemed to fit better than the others for assessment of low frequency noise annoyance.…”
Section: Rat~gsmentioning
confidence: 99%